Influence of a disinfectant based on polyhexamethylene guanidine hydrochloride on sanitary-indicatory microorganisms and on the white mice - Передера, С. Б.; Передера, Ж. О.; Щербакова, Н. С.; Держговська, Є. О. (Scientific Progress & Innovations, 2017)
The article presents the data relatively the analysis of the action of a disinfectant based on polyhexamethylene guanidine hydrochloride (PHMG-HC) on sanitary-indicatory microorganisms and on the white mice. We determined that a phenol coefficient of «PenaSept» in relation to S. aureus, E. coli is 7,4 and 5,9. Besides «PenaSept» shows a pronounced disinfectant activity. With a daily aerosol treatment for 14 days, the disinfectant is biosafety for the body of laboratory mice, which is proved on the basis of clinical and pathoanatomical studies.